Inhibition of canine duodenal interdigestive myoelectric complex by nutrient perfusion of jejunal and ileal Thiry-Vella loops. Issue 9 (September 1981) - Schang, J C; Angel, F; Lambert, A; Crenner, F; Aprahamian, M; Grenier, J F
Abstract : The mechanisms by which the intestinal interdigestive myoelectric complex (IDMEC), recurring at about 90 minute intervals in the fasted dog, is disrupted by feeding remain unknown. We investigated whether the IDMEC could be disrupted in the duodenum by perfusing a Thiry-Vella loop with glucose in the dog. An intestinal Thiry-Vella loop, measuring one half (80 to 160 cm) of the total length of the small bowel was constructed in four dogs from the jejunum, and in four other dogs from the ileum. Extracellular nichrome electrodes were sewn on the duodenum for recording the electrical activity of the intestine. After three weeks' recovery, electrical recordings were performed in the fasted dogs in order to observe whether the IDMEC persisted in the duodenum when the Thiry-Vella loops were perfused, at different days, for four hours with solutions made of either (1) NaCl 154 mM, (2) NaCl 308 mM, (3) glucose 300 mM, or (4) glucose 600 mM, at a rate of 8 ml/min. NaCl 308 mM and glucose 600 mM were also delivered at a rate of 4 ml/min. Glucose output from the Thiry-Vella loops was measured throughout the experiments over consecutive five minute intervals. Each experiment was performed three times in each dog. The results showed that perfusing the Thiry-Vella loops with NaCl 154 mM or NaCl 308 mM did not suppress the IDMEC in the duodenum whether the flow rate was 4 or 8 ml/min. On the contrary, perfusing the jejunal loops with glucose 300 mM disrupted the IDMEC in 54% of the experiments; perfusing glucose 600 mM disrupted the IDMEC in 83% of the experiments. In the ileal Thiry-Vella loop experiments, the IDMEC was disrupted in 33% of the cases with glucose 300 mM and in 66% of the cases with 600 mM. No significant difference was observed with glucose 300 mM delivered at a rate of 8 ml/min and glucose 600 mM delivered at a rate of 4 ml/min. Finally, the inhibitory effect of perfusing the Thiry-Vella loops with glucose increased as the amount of absorbed glucose increased. These results indicate that interruption of the IDMEC by feeding probably involves extraintestinal factors. These factors do not seem to be specific for any one part of the small intestine, but they seem to be activated by intestinal absorption.